2D Elasto-Plastic Finite Element Analysis of Tunnels in Dubai, UAE - Al Hai, Nasser (2012)
A Master of Science thesis in Civil Engineering by Nasser Al Hai entitled, "2 D Elasto-Plastic Finite Element Analysis of Tunnels in Dubai, UAE," submitted in June 2012. Thesis advisor is Dr. Zahid Khan . Available are both soft and hard copies of the thesis.